Performance Evaluation of Novel EV charging Topology for Standalone PV Systems with charge controller - Bondu, Pavan Kumar Reddy (2024)
This study explores the novel battery charging topology for standalone solar photovoltaic (PV) systems incorporating charge controller. The research leverages MATLAB/Simulink for modeling and simulation. In standalone PV systems, directly connecting batteries to PV modules can lead to detrimental overcharging or over-discharging, ultimately reducing battery lifespan. To mitigate this challenge, charge controllers are implemented. These intelligent devices regulate the output voltage and current from the solar panels, ensuring safe and efficient battery operation by preventing both overcharging and over-discharging. The analysis focuses on a PV-powered Single Ended Primary Inductor Converter topology alongside a modified version. These topologies integrate Perturb and Observe (P&O) and Incremental Conductance MPPT algorithms for optimal power extraction. The battery charge controller employs a three-stage strategy i.e., constant current, constant voltage absorption, and float charging to effectively manage the battery charging process. Performance evaluation considers MPPT tracking efficiency (achieving up to 98% under standard test conditions), battery charging effectiveness, and overall charge controller efficiency. The study aims to validate these results by benchmarking against a commercially available MPPT controller. The research concludes that the modified SEPIC topology with the implemented charge controller demonstrates superior suitability for EV charging applications compared to the standard SEPIC topology.